Enhancing mechanical performance and wet‐skid resistance of emulsion styrene butadiene rubber/natural rubber latex composites via in‐situ hybridization of silanized graphene oxide and silica. Issue 18 (4th January 2022) - Li, Qiao; Lin, Guangyi; Chen, Shouzhen; Zhang, Lin; Song, Yingjie; Geng, Chuanbao; Qu, Siyuan; Jing, Yuan; Liu, Fumin; Liang, Zhenning
Abstract: The wet skid resistance and thermal conductivity of "green tire" are the focus of research. In this work, through the use of different types of silane coupling agents, the surface of SiO2 and graphene oxide (GO) were grafted with amino and epoxy groups, respectively. The in‐situ generated SiO2 was grafted to the surface of GO by ring‐opening reaction of amino and epoxy groups. The emulsion styrene butadiene rubber/natural rubber latex (ESBR/NRL) composites were prepared by gas assisted spray flocculation process to improve the dispersion performance of hybrid filler. Because the surface of the hybrid filler contains amino and epoxy groups, it can be added as a reactive compatibilizer into the ESBR/NRL composites to improve the interface compatibility and synergistic reinforcement effect. Compared with the composites filled with SiO2, the composites filled with hybrid filler have excellent wet skid resistance and mechanical properties. When the mass ratio of GO to SiO2 is 3:10, the mechanical properties and wet skid resistance of rubber composites increase by 96.7% and 20.6%, respectively. Our preparation method of hybrid filler and flocculation process of rubber composites have broad application prospects in "green tire." Abstract :